2017
DOI: 10.1038/nature23642
|View full text |Cite
|
Sign up to set email alerts
|

Stromal R-spondin orchestrates gastric epithelial stem cells and gland homeostasis

Abstract: The constant regeneration of stomach epithelium is driven by long-lived stem cells, but the mechanism that regulates their turnover is not well understood. We have recently found that the gastric pathogen Helicobacter pylori can activate gastric stem cells and increase epithelial turnover, while Wnt signalling is known to be important for stem cell identity and epithelial regeneration in several tissues. Here we find that antral Wnt signalling, marked by the classic Wnt target gene Axin2, is limited to the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(198 citation statements)
references
References 27 publications
4
194
0
Order By: Relevance
“…It is reasonable to think that, similar to autocrine Rspo3, paracrine Rspo3 may also be involved in the activation of the Wnt/β‐catenin pathway and in the induction of cancer cell EMT and stemness. It has been shown that myofibroblast‐derived Rspo3 is required for the expression of Axin2 and Lgr5 in gastric epithelial stem cells . Moreover, both Wnt ligands and Rspo3 from platelet‐derived growth factor receptor alpha (PdgfRα)‐positive myofibroblasts are required to support the intestinal stem‐cell niche …”
Section: Wnt Signaling Is Involved In Epithelial‐stromal Crosstalk Ofmentioning
confidence: 99%
“…It is reasonable to think that, similar to autocrine Rspo3, paracrine Rspo3 may also be involved in the activation of the Wnt/β‐catenin pathway and in the induction of cancer cell EMT and stemness. It has been shown that myofibroblast‐derived Rspo3 is required for the expression of Axin2 and Lgr5 in gastric epithelial stem cells . Moreover, both Wnt ligands and Rspo3 from platelet‐derived growth factor receptor alpha (PdgfRα)‐positive myofibroblasts are required to support the intestinal stem‐cell niche …”
Section: Wnt Signaling Is Involved In Epithelial‐stromal Crosstalk Ofmentioning
confidence: 99%
“…Other toxins, such as VacA and CagL, as well as Hp components, such as LPS, also contribute to this malignant transformation. Recently, a group reported that Hp can promote GC by activating gastric stem cells . The gastric carcinogenesis initiated by Hp can be partially attributed to changes in signaling pathways, and the most studied pathways are toll‐like receptor‐4 (TLR‐4) and nuclear factor‐κβ (NF‐κB) signaling …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a group reported that Hp can promote GC by activating gastric stem cells. 32 The gastric carcinogenesis initiated by Hp can be partially attributed to changes in signaling pathways, and the most studied pathways are toll-like receptor-4 (TLR-4) and nuclear factor-κβ (NF-κB) signaling. 33,34 Activation of TLR-4 triggers a cascade of downstream signaling pathways, including phosphorylation of the mitogen-activated protein kinase (MAPK) pathway, which contains the components extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to local interactions, new research revealed the importance of longer‐range interactions to mediate gland hyperplasia which is a hallmark of H. pylori infection . Lineage tracing in the murine infection model revealed that H. pylori infection accelerates proliferation of an Axin2+ Lgr5‐ progenitor cell near the base of antral glands via induction of R‐spondin in underlying myofibroblasts.…”
Section: Helicobacter Pylori Gastric Colonizationmentioning
confidence: 99%